2009
DOI: 10.1016/j.devcel.2009.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Human Kinetochore Ska1 Complex Facilitates Microtubule Depolymerization-Coupled Motility

Abstract: Summary Mitotic chromosome segregation requires that kinetochores attach to microtubule polymers and harness microtubule dynamics to drive chromosome movement. In budding yeast, the Dam1 complex couples kinetochores with microtubule depolymerization. However, a metazoan homologue of the Dam1 complex has not been identified. To identify proteins that play a corresponding role at the vertebrate kinetochore-microtubule interface, we isolated a 3-subunit human Ska1 complex, including the previously uncharacterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
357
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(389 citation statements)
references
References 39 publications
27
357
3
Order By: Relevance
“…8,9 The kinetochore protein assemblies, from the inner towards the outer plate, contain the large constitutive centromere associated network (CCAN), consisting of approximately 14 proteins, and the KMN complex, which contains ten proteins in three subunits, called the Knl1, Mis12 and Ndc80 complexes. In addition to these components, which are required for microtubule binding, 10 there are many others that may stabilize microtubule binding, such as the Ska/ Rama complex, [11][12][13] or regulatory complexes like the chromosome passenger complex (CPC), 14,15 the RZZ complex 16 as well as additional proteins that control microtubule dynamics, 17 and other proteins. 1 One very important property of the kinetochore microtubule binding sites is that they have to be robust enough to withstand the pulling forces of the mitotic spindle without blocking the dynamic instability of microtubules.…”
Section: Spindly Switch Controls Anaphasementioning
confidence: 99%
“…8,9 The kinetochore protein assemblies, from the inner towards the outer plate, contain the large constitutive centromere associated network (CCAN), consisting of approximately 14 proteins, and the KMN complex, which contains ten proteins in three subunits, called the Knl1, Mis12 and Ndc80 complexes. In addition to these components, which are required for microtubule binding, 10 there are many others that may stabilize microtubule binding, such as the Ska/ Rama complex, [11][12][13] or regulatory complexes like the chromosome passenger complex (CPC), 14,15 the RZZ complex 16 as well as additional proteins that control microtubule dynamics, 17 and other proteins. 1 One very important property of the kinetochore microtubule binding sites is that they have to be robust enough to withstand the pulling forces of the mitotic spindle without blocking the dynamic instability of microtubules.…”
Section: Spindly Switch Controls Anaphasementioning
confidence: 99%
“…They further showed that in some successful cases, glass beads coated with reconstituted Ndc80 complex, a 57 nm long component of the core attachment site at kinetochores [149], could couple microtubule depolymerization to movement towards the minus-ends. This data suggest that the Ndc80 complex may correspond to the kinetochore fibrils observed by electron tomography, but that additional factors may be involved in microtubule depolymerization-coupled movement [150]. The use of "bonsai" forms of the Ndc80 complex that retain microtubule binding capacity but are only 15 nm long [151] should prove useful in determining the molecular nature of the kinetochore fibrils.…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 86%
“…This difference has been postulated to reflect the more stringent requirement for maintaining connection with the depolymerizing microtubule when a single point of attachment is present; thus, under these circumstances, the ring may provide necessary stability (Burrack et al, 2011;Thakur & Sanyal, 2011). Outside of the yeasts, sequence-based homologues of the Dam1 complex proteins are not identifiable, though a variety of evidence suggests that the functional homologue in metazoans may be the Ska complex (Gaitanos et al, 2009;Guimaraes & Deluca, 2009;Hanisch, Sillje, & Nigg, 2006;Jeyaprakash et al, 2012;Welburn et al, 2009). …”
Section: Introductionmentioning
confidence: 99%